2021
DOI: 10.1108/whatt-07-2021-0099
|View full text |Cite
|
Sign up to set email alerts
|

Residents' perceptions of the environmental and social impact of tourism in rural areas

Abstract: PurposeThis paper aims to provide an understanding of residents' perceptions of how tourism activity in a rural area impacts their environment as well as their economic and social lives individually and as a community.Design/methodology/approachAs a primary method of data collection, semi-structured interviews were conducted with 20 residents in the rural areas of Cyprus.FindingsThe study's findings suggest that tourism activity in the rural areas provides a plethora of opportunities to residents, but comes wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The emergence of ecosystem services and sustainability from 2018 to 2023 and from 2020 to 2023 also indicated that rural ecology and social and economic environment were paid more and more attention, especially their sustainability, in recent years. For example, Liasidou et al (2021) studied the impact of the tourism industry on rural society, and promoted the sustainable development of the rural areas in this regard. After rapid urbanization in a lot of developing countries, rural areas not only developed slowly but also lagged behind cities in many different aspects.…”
Section: Keyword Citation Burst Analysismentioning
confidence: 99%
“…The emergence of ecosystem services and sustainability from 2018 to 2023 and from 2020 to 2023 also indicated that rural ecology and social and economic environment were paid more and more attention, especially their sustainability, in recent years. For example, Liasidou et al (2021) studied the impact of the tourism industry on rural society, and promoted the sustainable development of the rural areas in this regard. After rapid urbanization in a lot of developing countries, rural areas not only developed slowly but also lagged behind cities in many different aspects.…”
Section: Keyword Citation Burst Analysismentioning
confidence: 99%
“…According to the World Tourism Organisation, sustainable tourism takes into account different dimensions that affect society from a present and future perspective including environmental, economic, and social impacts, as well as the well-being of the local population [45]. In other words, sustainability seeks to maximise the benefits of tourism activity without detracting from the available resources, in such a way that it results in an improvement, in all aspects, in the way of life of the resident population [17,46].Thus, the role of the local population in sustainability is essential. According to many authors, the development of sustainable tourism activity is only possible by integrating the resident population in the development of tourism policies [19,[47][48][49].…”
Section: Geotourism and Sustainable Developmentmentioning
confidence: 99%
“…On the other hand, tourism activity in popular destinations undoubtedly affects the way of life of the resident population, whose perceptions will vary according to the impact it has on their socio-economic environment [17]. Furthermore, knowledge of the perceptions of the local population is a crucial aspect of sustainable tourism management [18][19][20], which is even more relevant in a natural destination such as a geopark [21].…”
Section: Introductionmentioning
confidence: 99%